Effect of biogas effluent from pig manure and Longan (Dimocarpus longan) residues on growth of Marigold (Tagetes erecta) - Prathumyot, W.; Makboon, R.; Yota, M.; Chakhatrakan, S.; Matta, F. B.; Chitaree, L. (International Journal of Agricultural Technology, 2019)
The efficiency of biogas effluent fermented with pig manure and longan residues on growth of marigold was investigated. Treatments were control (no fertilizer), and four concentrations (10%, 20%, 30% and 40%) of biogas effluent and chemical fertilizer. Plants were watered with 200 ml of each biogas effluent concentrationt every 4 days. Chemical fertilizers were applied as 15-15-15 and 8-24-24. Results showed that the growth of marigold in the control was lowest as compared to the other treatments. There was no significant difference in the plant height, stem diameter, bush diameter, fresh weight of blooming flowers and initiation of first flower between biogas effluents and chemical fertilizer. Fresh weight of whole plant and number of blooming flowers resulting from the chemical fertilizer treatment was highest compared to the control and effluent treatments. Dry weight of whole plant resulting from the chemical fertilizer treatment was not significantly different compared to 10%, 20% and 30% biogas effluent treatments. Total chlorophyll and chlorophyll per unit leaf area in the chemical fertilizer did not differ as compared to 30% and 40% biogas effluent treatments.